2015
DOI: 10.1057/jos.2014.15
|View full text |Cite
|
Sign up to set email alerts
|

System dynamics modelling to support policy analysis for sustainable health care

Abstract: System Dynamics (SD) is an established simulation methodology used to explore the behavior of social systems over time. The field has addressed challenging sustainability problems in fisheries, urban planning, and environmental resource management. It has also been successfully applied to healthcare, in chronic disease modelling and workforce planning. This paper presents system dynamics models of healthcare sustainability, and illustrates two complementary applications of SD: (i) continuous simulation of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…(1) Population influences the economics and environment of cities through aspects such as labor force, consumption of entertainment, and tourist recreation [46,47]. Population changes are also based on feedback principles and are influenced by economic development, environmental changes, and urban CES [48].…”
Section: Sd Modellingmentioning
confidence: 99%
“…(1) Population influences the economics and environment of cities through aspects such as labor force, consumption of entertainment, and tourist recreation [46,47]. Population changes are also based on feedback principles and are influenced by economic development, environmental changes, and urban CES [48].…”
Section: Sd Modellingmentioning
confidence: 99%
“…The authors concluded that advances in software are allowing the participatory model building approach to be extended to more sophisticated multimethod. Lyons and Duggan (2015) investigated the use of system dynamics modeling to support policy analysis for sustainable health care. They present two contributions compared to other works: the continuous simulation of health-care infrastructure adequacy and the conceptual modeling of the wider public policy context for health-care sustainability.…”
Section: System Dynamics Applicationsmentioning
confidence: 99%
“…We conduct an extensive simulation study with the intention to fill this gap. We use "system dynamics" as the modeling methodology in this study (Barlas, 2002;Barlas and Yasarcan, 2006;Flood, 2010;Forrester, 1961;Kunsch, Theys, and Brans, 2007;Lyons and Duggan, 2014;Pedamallu et al, 2012;Sterman, 2000). …”
Section: Increases Via Acquisition Flow and Decreases Via Loss Flow mentioning
confidence: 99%